Optimizing Wordwall Media in Arabic Language Learning: An Experimental Study on Mastery of Ismiyyah and Fi'liyah Sentences - Alfina, Alfina; Subhan, Subhan; Ubaidillah, Ubaidillah (Universitas Yudharta Pasuruan, 2025)
Wordwall affected students' mastery of Arabic sentence structure at MTs Negeri 2 Kota Serang, particularly in terms of the number of ismiyyah and fi'liyah. This study not only measured the effect of Wordwall but also examined how to optimize its use by integrating appropriate game types and feedback features to enhance students’ mastery of ismiyyah and fi‘liyah sentence structures. Traditional teaching methods and the lack of interactive digital media resulted in low syntactic ability among students, which motivated this study. Wordwall, a game-based learning platform, is considered to be able to increase student engagement and understanding through visual and audio activities and instant feedback. A quantitative method with a One Group Pretest-Posttest quasi-experimental design was used in this study. The research sample consisted of 32 students. The tools used included learning outcome tests and perception questionnaires, which had been tested for validity and reliability using the SPSS program. The results showed a significant increase in the mastery of Arabic sentence structure, with an average pretest score of 53.66 and a posttest score of 93.25, and a paired sample t-test showed a significance value of p = 0.000. On the other hand, Cohen's effect size of 3.66 indicated a very large practical effect. The high survey results show that students' perceptions of the use of Wordwall are also positive. Based on the research that has been conducted, Wordwall can be used as a digital learning tool in madrasahs and has a significant impact on students' mastery of Arabic sentence structure.